Patterns of use and perceptions of harm of smokeless tobacco in Navi Mumbai, India and Dhaka, Bangladesh - Seema Mutti; Jessica L Reid; Prakash C Gupta; Mangesh S Pednekar; Gauri Dhumal; Nigar Nargis; AKM Ghulam Hussain; David Hammond (Wolters Kluwer Medknow Publications, 2016)
Background: Globally, smokeless tobacco use is disproportionately concentrated in low-income and middle-income countries like India and Bangladesh. Objectives: The current study examined comparative patterns of use and perceptions of harm for different smokeless tobacco products among adults and youth in Navi Mumbai, India, and Dhaka, Bangladesh. Methods: Face-to-face interviews were conducted on tablets with adult (19 years and older) smokeless tobacco users and youth (16-18 years) users and non-users in Navi Mumbai (n = 1002), and Dhaka (n = 1081). Results: A majority (88.9%) of smokeless tobacco users reported daily use. Approximately one-fifth (20.4%) of the sample were mixed-users (used both smoked and smokeless tobacco), of which about half (54.4%) reported that they primarily used smokeless over smoked forms like cigarettes or bidis. The proportion of users planning to quit was higher in India than in Bangladesh (75.7% vs. 49.8%p " 0.001). Gutkha was the most commonly used smokeless product in India, and pan masala in Bangladesh. Among users in Bangladesh, the most commonly reported reason for using their usual product was the belief that it was "less harmful" than other types. Perceptions of harm also differed with respect to a respondent's usual product. Bangladeshi respondents reported more negative attitudes toward smokeless tobacco compared to Indian respondents. Conclusions: The findings highlight the high daily use of smokeless tobacco, and the high prevalence of false beliefs about its harms. This set of findings reinforces the need to implement effective tobacco control strategies in low and middle-income countries like India and Bangladesh.